2015
DOI: 10.17523/bia.v72n2p163
|View full text |Cite
|
Sign up to set email alerts
|

Suplementação de enzimas amilase, fitase e protease para codornas japonesas em postura

Abstract: 1 Recebido para publicação em 05/11/14. Aceito para publicação em 15/06/15. 2 Universidade Federal de Lavras (UFLA), Departamento de Zootecnia, Lavras, MG, Brasil. *Autor correspondente: josimarsantrib@hotmail.com RESUMO: O objetivo deste trabalho foi avaliar os efeitos da suplementação das enzimas amilase, fitase e protease de formas isoladas e em associação, em dietas para codornas japonesas em postura. Foram utilizadas 300 codornas, distribuídas em um delineamento inteiramente ao acaso, com cinco tratamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 1 publication
3
5
0
6
Order By: Relevance
“…Furthermore, because the evaluations were done with fresh eggs, the effect of the storage time on these eggs could not be evaluated, because in general, albumen quality is more influenced by time and storage resistance. The data agree with those reported by Ribeiro et al (2015), who found no changes in the percentage parameters of clear areas when adding phytase in the diet of laying quails. Similarly, Rezende et al (2013), when evaluating the inclusion of phytase in the diet of light laying hens, found no differences in the evaluation of the Haugh units of poultry eggs.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, because the evaluations were done with fresh eggs, the effect of the storage time on these eggs could not be evaluated, because in general, albumen quality is more influenced by time and storage resistance. The data agree with those reported by Ribeiro et al (2015), who found no changes in the percentage parameters of clear areas when adding phytase in the diet of laying quails. Similarly, Rezende et al (2013), when evaluating the inclusion of phytase in the diet of light laying hens, found no differences in the evaluation of the Haugh units of poultry eggs.…”
Section: Resultssupporting
confidence: 92%
“…The performance results are presented in Table 2, demonstrating no differences in production(P=0.920) or egg weight (P=0.166).The behavior observed in the present study corroborates the efficacy of phytase effects in making phytic phosphorus available, and it is possible to reduce the levels of total phosphorus of the rations without altering egg production. A similar result was reported by Lima et al (2011) The results agree with those of Zahran et al (2012) and Ribeiro et al (2015) who worked with laying quails, with those of Resende (2013) and Ferreira et al (2015), who worked with light laying hens, and with those of Sacakli et al (2005), Blake & Hess (2013) and Pirzado et al (2016) who worked with broiler quails; none found differences in terms of egg production or egg weight, supplemented or not with phytase. The absence of significant differences in performance data can be explained in part by the 21-day experimental period used, because birds have phosphorus reserves in the bones, and the period may not have been long enough to promote reduction or phosphorus deficiency in quails, with a consequent fall in yield.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…No Brasil, as rações para frangos de corte são constituídas basicamente por milho e farelo de soja (Ribeiro et al, 2015) em média de 60 e 40%, respectivamente (Cardoso et al, 2011) contribuindo com a maior parte do custo da produção (Miranda et al, 2017).…”
Section: Introductionunclassified